Long-term renal outcomes comparison between patients with chronic kidney disease and hepatorenal syndrome after living donor liver transplantation - Tseng, Hsiang-Yu; Lin, Yu-Hung; Lin, Chih-Che; Chen, Chao-Long; Yong, Chee-Chien; Lin, Li-Man; Wang, Chih-Chi; Chan, Yi-Chia (Frontiers in Surgery, 2023)
Background and aims: Hepatorenal syndrome (HRS) is a disastrous renal complication of advanced liver disease with a poor prognosis. Restoring normal liver function through liver transplantation (LT) is a standardized treatment with favorable short-term survival. However, the long-term renal outcomes in patients with HRS receiving living donor LT (LDLT) are controversial. This study aimed to investigate the prognostic impact of LDLT in patients with HRS. Methods: We reviewed adult patients who underwent LDLT between July 2008 and September 2017. Recipients were classified into 1) HRS type 1 (HRS1, N=11), 2) HRS type 2 (HRS2, N=19), 3) non-HRS recipients with pre-existing chronic kidney disease (CKD, N=43), and 4) matched normal renal function (N=67). Results: Postoperative complications and 30-day surgical mortality were comparable among the HRS1, HRS2, CKD, and normal renal function groups. The 5-year survival rate was >90% and estimated glomerular filtration rate (eGFR) transiently improved and peaked at 4 weeks post-transplantation in patients with HRS. However, renal function deteriorated and resulted in CKD stage ≥III in 72.7% of HRS1 and 78.9% of HRS2 patients (eGFR <60 ml/min/1.73 m2). The incidence of developing CKD and end-stage renal disease (ESRD) was similar between the HRS1, HRS2, and CKD groups, but significantly higher than that in the normal renal function group (both P<0.001). In multivariate logistic regression, pre-LDLT eGFR <46.4 ml/min/1.73 m2 predicted the development of post-LDLT CKD stage ≥III in patients with HRS (AUC=0.807, 95% CI=0.617-0.997, P=0.011). Conclusions: LDLT provides a significant survival benefit for patients with HRS. However, the risk of CKD stage ≥III and ESRD among patients with HRS was similar to that in pre-transplant CKD recipients. An early preventative renal-sparing strategy in patients with HRS is recommended.